Pengaruh Konseling MPASI Terhadap Perilaku Ibu Dalam Memberikan MPASI Pada Bayi Usia 0-6 Bulan di Desa Tempursari Kecamatan Kedungjajang - Laili, Siti Rohmatul; Suhartini, Titik (Jurnal Keperawatan Muhammadiyah, 2023)
Digestive disorders, allergic diarrhea and digestive tract infections are the effects of giving complementary foods too early. MPASI should be given to babies over the age of 6 months. At the age of over 6 months, the baby's stomach is good and is able to digest food properly. One of the efforts that can be made to overcome early complementary feeding is through counseling activities. The purpose of this writing is to analyze the effect of complementary breastfeeding counseling on mothers' behavior in giving complementary foods to infants aged 0-6 months in Tempursari Village, Kedungjajang.. The research design used pre-experimental research. This research was carried out using a pre post test design. The population of this study were all mothers who had babies aged 0-6 months in the Tempursari Village, Kedungjajang. The sampling technique used was total sampling technique with a sample size of 27 people in this study. Collecting data used questionnaire and processing the data through editing, coding, scoring and tabulating used the Wilcoxon SPSS test. The results of the analysis of mother's behavior in giving solids before counseling showed that most of the mothers' behavior in giving complementary foods was inappropriate for infants aged 0-6 months as many as 19 people (70.4%). While the results of the analysis of mother's behavior in giving solids after counseling showed that most of the mother's behavior in giving appropriate solids to infants aged 0-6 months was 23 people (85.2%). The results of the Wilcoxon statistical test on mother's behavior in giving complementary foods to infants aged 0-6 months (p value = 0.000) obtained a p value <0.05, so it can be concluded that there is a significant influence on mother's behavior in providing complementary foods to infants aged 0-6 months before and after being given MPASI counseling. The results of this study indicate that good counseling can improve the accuracy of the mother's behavior in giving complementary foods to her baby so that it will have an impact on the health and growth of her baby.